Assesment of trace element status in common goat feeds and in vital body tissues of Black Bengal bucks (Capra hircus) with special reference to chromium - Paul, T K; Ghosh, T K; Haldar, S (The Indian Journal of Animal Sciences, 2005)
A field survey was conducted in 3 villages of the new alluvial agro-climatic zone of West Bengal to ascertain th satus ofchromium and some trace elements, viz., copper, zinc. iron and manganese in soil and common goat feeds. Concentration of Cr and that of the aforesaid trace elements was determined in the plasma, liver, kidney and important muscles of Black Bengal bucks as well. Soil Cr ranged from 1.05 to 2.30 mg/kg DM, while Cu, Zn, Fe and Mn in soil were within the normal ranges of variation. In the natural pasture (Cynodon dactylon) Cr concentration ranged between 0.15 to 0.60 mg/ kg DM. In green roughage and concentrate mixtures Cr concentration was higher than that in the pasture grass. The mean concentration of Cr in the plasma of the Black Bengal bucks was 0.056±0.002 µg/ml. The concentration of the sameelement in liver and kidney was 0.113±0.006 and 0.068±0.004 mg/kg fresh weight (FW) respectively. Concentration of Cr (mg/kg FW) varied little amongst neck muscle, quadriceps femoris, triceps and trapezious. Cu, Zn. Fe and Mn in plasma were 0.89±0.024, 1.13±0.047, 1.59±0.060 and 0.23±0.011 µg/ml respectively. Concentration of these trace elements was within the normal range of variation in the liver, kidney and muscles of the bucks. The study revealed that concentration of Cr in plasma and different body tissues of bucks could be maintained even without any supplemental Cr though marginal deficiency of Cu, Zn and Mn was observed despite adequacy of these mineral elements in the feeds and fodder.